EFFECT OF BOILING CARICA PUBESCENS SEEDS ON ANTINUTRIENT CONTENT AND IN VITRO NUTRIENT DIGESTIBILITY - Rahma Wulan Idayanti; Tatik Rohani; Fendi Yayuki; Alfian Nur Syahrul; Ajeng Ayu Saputri; Endang Puji Lestari; Agung Purnomoadi; Endang Purbowati; Mukh Arifin Hadi (SEAMEO BIOTROP, 2024)
This research was conducted to determine the chemical composition and anti-nutritional content of Carica Dieng seeds (Carica pubescens) and their in vitro digestibility after boiling. The process of boiling is frequently employed to reduce antinutrient content and increase the digestibility of nutrients. This research used a completely randomized design, consisting of three treatments with boiling durations of 0, 10, and 20 minutes, each repeated six times. The research revealed a significant (p<0.05) decrease in the tannin and saponin levels of Carica Dieng seeds following the boiling process. The concentration of carica seed tannin was lowered to a range of 36-48%, while the saponin content decreased by 52-58%. Subsequently, a descriptive analysis was conducted to assess the nutritional and amino acid composition of the seeds after boiling them for a duration of 10 minutes. Lysine (1.57% w/w) dominated the essential amino acids in Carica pubescens seeds, and glutamic acid (3.19% w/w) dominated the non-essential amino acids The digestibility of boiling carica seeds as feed was assessed by including them into complete feed at different proportions: 0% (T0), 5% (T2), 10% (T3), and 15% (T4). This experiment followed a Completely Randomized Design with five replications. The variables included in-vitro dry matter (DMD) and organic (OMD) digestibility. The DMD of carica seeds at a concentration of 0% showed a statistically significant difference (p<0.05) when compared to the addition of 5% carica seeds. However, there was no significant difference in DMD between adding carica seeds at levels of 10% and 15% in the total meal. The organic material digestibility variable showed that the treatment without carica seeds was not significantly different from adding 10% carica seeds but was substantially different from adding 5 and 15% carica seeds. Carica pubescens seed supplementation of up to 10-15% remains viable for inclusion in whole feed since it does not reduce digestibility.